Resting-state EEG, impulsiveness, and personality in daily and nondaily smokers. Issue 1 (January 2016) - Rass, Olga; Ahn, Woo-Young; O'Donnell, Brian F.
Highlights: Resting EEG in non-deprived smokers may be a biomarker for nicotine use severity. Smokers report higher impulsiveness and lower conscientiousness than nonsmokers. Sensory hedonia may play a role in nondaily smoking. Abstract: Objectives: Resting EEG is sensitive to transient, acute effects of nicotine administration and abstinence, but the chronic effects of smoking on EEG are poorly characterized. This study measures the resting EEG profile of chronic smokers in a non-deprived, non-peak state to test whether differences in smoking behavior and personality traits affect pharmaco-EEG response. Methods: Resting EEG, impulsiveness, and personality measures were collected from daily smokers ( n = 22), nondaily smokers ( n = 31), and non-smokers ( n = 30). Results: Daily smokers had reduced resting delta and alpha EEG power and higher impulsiveness (Barratt Impulsiveness Scale) compared to nondaily smokers and non-smokers. Both daily and nondaily smokers discounted delayed rewards more steeply, reported lower conscientiousness (NEO-FFI), and reported greater disinhibition and experience seeking (Sensation Seeking Scale) than non-smokers. Nondaily smokers reported greater sensory hedonia than nonsmokers. Conclusions: Altered resting EEG power in daily smokers demonstrates differences in neural signaling that correlated with greater smoking behavior and dependence. Although nondaily smokers share some characteristics with daily smokers that may predict smoking initiation and maintenance, they differ on measures of impulsiveness and resting EEG power. Significance: Resting EEG in non-deprived chronic smokers provides a standard for comparison to peak and trough nicotine states and may serve as a biomarker for nicotine dependence, relapse risk, and recovery.